Synthesis of Isatin Derivative on the Short Multiwalled Carbon Nanotubes and Their Effect on the MKN-45 and SW742 Cancer Cells - Hasan Tahermansouri; Farshid Chitgar (Journal of Chemistry)
The carboxylated short multiwalled carbon nanotubes (Sh-MWCNT-COOH) were first modified by isatin derivative to form Sh-MWCNT-Amide and then by hydrazine to produce Sh-MWCNT-Spiro. All products were characterized by the Fourier transform infrared spectroscopy, Raman spectroscopy, scanning electron microscope, elemental analysis, thermogravimetric analysis, derivative thermogravimetric, solubility test, and cellular investigations. This functionalization has been chosen due to active sites of OH and carbonyl groups in Sh-MWCNT-Amide which might be used as functional materials in the future. Toxicity of these samples was evaluated with human gastric and colon cancer cells, and killed cell numbers were measured by reduction of living cells with 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyltetrazolium bromide. Cellular results showed high toxicity of Sh-MWCNT-Amide in all samples investigated.